Methadone rotation for cancer pain: an observational study. Issue Volume 12:Issue e6(2022) (22nd April 2020) - Tan, Christina; Wong, Jade Fui; Yee, Choon Meng; Hum, Allyn
Abstract : Context: Methadone is a useful option in the treatment of cancer pain. Despite its advantages, methadone use is complicated due to high interindividual variability in pharmacokinetics. Various rotation methods from other opioids have been proposed in mostly Caucasian populations. Objectives: This study aims to describe our experience with opioid rotation to methadone for management of cancer pain in a predominantly Asian population. Methods: A retrospective review of 52 inpatients initiated on methadone for cancer pain from June 2015 to June 2018 was conducted. Our institution protocol for methadone rotation involves either one of two methods ('Stop-and-go' or the Edmonton 3-day rotation) based on the morphine-equivalent daily dose (MEDD), using an equianalgesic ratio of 10:1 for MEDD <1000 mg. To account for incomplete cross-tolerance, we further reduce the calculated dose by 30%. Results: The majority of patients had mixed nociceptive-neuropathic pain (83%) and the predominant reason for methadone rotation was ineffective analgesia with other opioids (75%). The median MEDD before rotation was 104 mg. Effective analgesia (defined as a decrease in numerical rating scale (NRS) of ≥1 or attainment of NRS ≤3) was achieved within 3 days after rotation in 89% of patients. Patients with an MEDD ≤100 mg/day required a greater degree of uptitration of methadone dose after rotation compared with those with an MEDD >100 mg/day. Conclusion: Rotation to methadone according to our protocol is effective in achieving adequate analgesia in most patients experiencing nociceptive-neuropathic pain. Our results also suggest that a fixed equianalgesic ratio of 10:1 may be adequate for patients at low-to-moderate MEDD <400 mg/day.